Direct endovascular treatment versus bridging therapy in patients with acute ischemic stroke eligible for intravenous thrombolysis: systematic review and meta-analysis. (4th August 2021) - Zhang, Jian; Chen, Shijian; Shi, Shengliang; Zhang, Yueling; Kong, Deyan; Xie, Yiju; Deng, Xuhui; Tang, Jian; Luo, Jinglian; Liang, Zhijian
Abstract : Objective: In this review and meta-analysis we sought to compare the efficacy and safety of direct endovascular thrombectomy (EVT) and bridging therapy for intravenous thrombolysis (IVT)-eligible patients with acute ischemic stroke caused by large vessel occlusions (AIS-LVO). Methods: We searched Medline, Embase, and the Cochrane Library for published randomized clinical trials (RCTs) and observational studies providing outcomes of patients with IVT-eligible AIS-LVO who have undergone EVT with or without IVT. The primary outcome was the proportion of patients achieving a modified Rankin Scale (mRS) score of 0–2 at 90 days. The secondary outcomes included the rates of (1) an excellent outcome defined as an mRS score of 0 or 1 at 90 days, (2) mortality at 90 days, (3) symptomatic intracranial hemorrhage (sICH), (4) any type of intracranial hemorrhage (ICH), (5) successful recanalization, and (6) clot migration. Results: We included three RCTs and six observational studies (4 of which were propensity score-adjusted studies) with a total of 3133 patients. In unadjusted and adjusted analyses, no differences in the rates of mRS scores 0–2, mRS scores 0–1, mortality at 90 days, sICH or successful recanalization were detected between patients with AIS-LVO who underwent direct EVT or bridging therapy. The patients treated with direct EVT had a lower risk ratio for any type of ICH and clot migration than did the patients treated with bridging therapy. Conclusion: Compared with bridging therapy, direct EVT may be equally effective and yield a lower rate of ICH and clot migration in patients with AIS. Trail registration number: PROSPERO: CRD42021236691.